Global connections between development and finance - Horacio Ortiz (economic sociology. perspectives and conversations, 2024)
At least since the 1980s, development policies and narratives promoted by institutions such as the International Monetary Fund and the World Bank have been shaped by the idea that development could be better achieved if economic practice and social organization more generally were articulated mainly through markets, relegating states to mere guarantors of the rules of exchange. This imaginary has given a central role to the financial sector, presented as a marketplace in which free investors are able to invest in financial assets, extending credit and monetary resources in a socially optimal way thanks to the mechanism of informational market efficiency.
Keywords: 300